Pelvic congestion syndrome as a cause of chronic pelvic pain - N. Yu. Novikova; V. I. Tsibizova; P. D. Puzdriak; E. V. Komlichenko; I. G. Tsnobiladze; A. V. Malushko; M. A. Ivanov; K. A. Chizhova; P. B. Bondarenko; I. M. Kositsyna; D. V. Blinov (IRBIS LLC, 2021)
Altered pelvic venous circulation, which may occur due to pelvic venous congestion and varicose veins of the vulva, may be among the causes for developing chronic pelvic pain syndrome. Pelvic congestion syndrome (PCS) is characterized by chronic discomfort in the pelvic area, which may be aggravated during coitus or acquire orthostatic position, and result in severe dysfunction of the pelvic organs. Varicose veins of the vulva develop due to obstruction of the veins, increased venous pressure, and venous insufficiency in the pelvis. Varicose veins may be isolated or associated with varicose veins of the lower extremities. The diagnosis and treatment of such patients are limited by the lack of definitive clinical criteria for early diagnostics, which were discussed in the current study.